Agrochemicals' effects on functional feeding groups of macroinvertebrates in Pampas streams. (June 2019) - Solis, M.; Arias, M.; Fanelli, S.; Bonetto, C.; Mugni, H.
Highlights: Nutrients and endosulfan concentrations were higher in streams adjacent to crops. Total invertebrate abundance and taxonomic richness were lower in cropped sites. Shredders were dominant at the reserve and livestock streams. Scrapers and predators were dominant at the cultivated sites. Land use is causing change in functional feeding groups' composition. Abstract: The use of agrochemicals in Argentina has increased over the last decades and may represent an environmental risk for adjacent water bodies. In this work we study the invertebrate assemblages in nine streams sampled at 11 sites with different land use on the adjacent plots in the years 2011–2014. Four sites were located inside a biosphere reserve, 4 sites were located adjacent to livestock plots and the other 3 sites were adjacent to cropped plots. The taxa composition was assessed and sorted into functional feeding groups: shredders, gatherers, filterers, scrapers and predators. Significant differences were detected among the functional feeding groups according to the use given to the adjacent land. Total density and taxonomic richness were significantly higher in the streams next to the reserve and livestock sites than in those adjacent to cropped plots; there were no differences between the first two. Gatherers and shredders density was significantly higher in the reserve and livestock than in the cropped sites. Scrapers and predators were the best represented at the cropped sites. Nutrient concentrations in water and endosulfan concentrations in the bottom sediments were also higher at the cultivated sites, suggesting that agrochemical loads from land cultivation caused the observed differences in composition.